Safety and Clinical Responses in Ankylosing Spondylitis after Three Months of Etanercept Therapy - Choi, Chan-Bum (The Korean Academy of Medical Sciences, 2008)
We aimed to evaluate the safety and clinical responses in Korean ankylosing spondylitis (AS) patients after three months of etanercept therapy. AS patients satisfying the Modified New York Criteria were enrolled. They were assessed for safety and clinical responses at enrollment and after three months of etanercept therapy. A total of 124 patients completed the study. After three months, the rate of ASsessment in AS International Working Group 20% improvement (ASAS 20) response was 79.8%. The rates of ASAS 40 and ASAS 5/6 responses were 58.5 and 62.8%, respectively. Significant improvement of Korean version of Bath AS Disease Activity Index (KBASDAI) (p<0.0001), Bath AS Functional Activity Index (BASFI) (p<0.0001), and Bath AS Metrology Index (BASMI) (p=0.0009) were achieved after three months. Quality of life was also significantly improved after three months, as demonstrated by scores for SF-36 (p<0.0001) and EQ-5D (p<0.0001). Erythrocyte sedimentation rate and C-reactive protein were significantly decreased (p<0.0001, p<0.0001, respectively). None of the patients developed tuberculosis and there were no serious adverse event. AS patients with inadequate response to conventional therapy showed significant clinical improvement without serious adverse events after three months of etanercept therapy.